Study on Numerical Simulation Test of Mining Surface Subsidence Law under Ultrathick Loose Layer. (10th May 2021) - Shi, Weiping; Qu, Xiaocheng; Jiang, Chuntao; Li, Kaixin
Abstract : In the process of coal mining, the surface subsidence under ultrathick loose layer is abnormal (subsidence coefficient greater than 1.0), which will cause great damage to the surface ecological environment. The fracture propagation and stress evolution of bedrock are of great significance to the prevention of surface subsidence. Taking the 1305 working face of a mine as the background, this paper study the process of crack propagation and stress evolution of bedrock under the influence of ultrathick loose layer by methods of on-site measurement, similar simulation, and numerical simulation. During the research process, the physical model was verified by the measured data. Then, the numerical model was verified by the crack propagation angle and subsidence of bedrock, which were obtained in a similar simulation. Based on the verified numerical model, it was obtained that after the coal seam was mined out, the bedrock above the mined-out area was mainly damaged by tension, while the strata on both sides of the crack expansion angle were mainly damaged by shear and tension. During coal seam mining, for bedrock the process of fracture expansion, subsidence, and stress evolution all could be divided into four stages. This research provides a basis for the control of surface subsidence.